The mental health of health professionals during the COVID-19 pandemic: an integrative review (Research, Society and Development, 2022)
The present scenario of COVID-19 pandemic provoked intense changes in the lives and work dynamics of health professionals. This work category started to live with constant exposure to SARS-CoV-2 virus, which had impact on the routine and mental health of this group. To that extent, the objective of this study was to analyze the main factors that influenced the mental health of health personnel during the current COVID-19 pandemic. This study is an integrative literature review, based on the guiding question: How has COVID-19 pandemic impacted on the mental health of health professionals? The research was made on the databases of SciELO, LILACS and PubMed, using the descriptors: “Mental health”, "Health personnel” and “COVID-19”, indexed according to DeCS and combined using the boolean operator “AND”. Only articles published between 2020 and 2022 were considered. From the inclusion criteria, 10 articles were selected to develop this review, whereby the main aspects related to the psychic suffering of health professionals during the pandemic were identified, such as exposure to the disease, gender issues, increased workload, overload, excessive exposure to information, social isolation, area of activity, lack of PPE and age group. Therefore, the analyzed articles highlighted psycho-emotional impacts, among which the development of stress, anxiety, depression, and sleep disorders were the most frequent ones.